PENGARUH FILSAFAT ANALITIK DALAM PENDIDIKAN BAHASA PRANCIS - Rohali, Rohali (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2019)
(Title: Effects of Analytic Philosophy on French Language Education). Language learning cannot be separated from philosophy, because philosophy is the mother of science. In its development, language learning was influenced by the philosophy that developed in his day, including analytic philosophy. The influence of analytic philosophy is strongly felt in language education, especially in semantic and pragmatic studies. The theory of logical atomism put forward by Russell has opened new horizons in the study of science, including linguistics. Meanwhile, the theory of meaning is picture which is then continued with the theory of meaning is use by Wittgenstein is a forerunner to semantic and pragmatic studies. In addition, the analytic philosophy developed by the Oxford school has developed a theory of speech acts which naturally influences language learning, from language learning to language education as speech acts. Keywords: philosophy, analytic, french, pragmatics